Indeks Subjek Volume 36, Tahun 2016 - Indeks Subjek Volume 36, Tahun 2016 (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
ACEI activity 170Acetobacter aceti 411Acid 404Activation energy (Ea) 176Adsorbed carrier solid-state fermentation 254Agroindustry 206Allergy 450Amino-acid 56Amylograph 302Anaerobic digestion 80Analytical evaluation 308Anthocyanin 261Antibacterial 379Antioxidant 30, 137Antioxidant activity 261ARIMA model 475Ascorbic acid 270